VECTOR BOND GRAPH METHOD FOR UNIFIED MODELING AND SIMULATION OF JAW CRUSHER SYSTEM DYNAMICS - WANG ZhongShuang; ZHOU QianBin; SHI YongZhen (Jixie qiangdu)
Aiming at the problem of unified modeling and simulation of system dynamics of simple swing jaw crusher driven by electric motor, the corresponding vector bond graph method was proposed. According to the constraint relation of the kinematic pair of the mechanism, the vector bond model of each component was bonded to each other, and the vector bond graph model of a six bar simple swing jaw crusher mechanism was made. By acting on the constraint force vectors of kinematic pair as the effort source vector at the corresponding 0-junction, the energy storage elements of the mechanism vector bond graph model were made have integral causality. Based on this, the vector bond graph model of the simple swing jaw crusher system was made, which takes into account the driving motor, crushing resistance force and the constraint force vector of the kinematic pair, and the unified computer modeling and dynamic simulation of the electromechanical system were realized. Compared with the results calculated by Newton-Euler dynamics method, the reliability of the proposed method was verified. The results show that the method described in this paper is effective, and its stylized modeling method improves the automation degree and reliability of electromechanical system dynamics modeling and simulation. In a movement cycle, the positive and reverse maximum of angular velocity for jaw crushing stroke and discharging stroke have little difference, and the time of crushing stroke and discharging stroke is close. At the beginning and the end of a motion cycle, the angular acceleration of the moving jaw and the constrained reaction force at both ends of the moving jaw will change greatly. In the final stage, the angular acceleration of the moving jaw increases from 0 to-83.36 rad/s~2, and the growth rate of the constrained reaction force at both ends is 2 576.44% and 249.10%, respectively. In addition, when the jaw is in the left limit position, the abrupt change of crushing force leads to large abrupt change of constrained reaction force at both ends of the jaw, with the reduction rates of 95.84% and 72.43%, respectively. This lays a foundation for the optimal design of the structure and parameters of the crusher, and further shows that the method presented in this paper has distinct characteristics and advantages.